Does Sagittal Spinopelvic Configuration Influence Vertebral Fracture Type or Localization in Trauma Patients?: A Retrospective Radiologic Analysis. Issue 3 (April 2017) - Bouaicha, Samy; Cunier, Marc; Scheyerer, Max J.; Wanner, Guido A.; Simmen, Hans-Peter; Werner, Clément M.L.
Abstract : Study Design: Retrospective data analysis. Objective: The aim of this study was to analyze correlations between spinopelvic configuration and fracture pattern or location in traumatic vertebral fractures. Summary of Background Data: The spinopelvic configuration represented by the pelvic incidence (PI) angle showed to have a strong correlation with the occurrence of degenerative diseases of the thoracolumbar spine. No data are available on whether there is an influence of the PI angle on traumatic vertebral lesions as well. Materials and Methods: In a consecutive series of patients sustaining traumatic vertebral fractures, we retrospectively analyzed spinopelvic computed tomography data sets of 197 patients (121 male and 76 female patients; mean age, 51 years). Measurements included the PI angle, level of fracture(s), and fracture type according to the AO classification. Statistical analysis was performed to calculate correlation between PI and fracture level and between PI and fracture type. Results: An average of 1.6 fractures per patient was found in the 197 individuals included in our study. PI angle showed a mean of 50.6 degrees for the left hip and a mean of 49.9 degrees for the right hip. There were no significant differences of the PI angle between male and female patients as well. Neither a significant effect of the PI angle on the vertebral fracture level ( P =0.64) nor a significant relationship between the PI angle and the fracture type according to the AO classification ( P =0.52) was found. Conclusions: The spinopelvic configuration represented by PI angle seems to influence neither the level nor the type of vertebral fractures in trauma patients.